(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this present innovatively superfast world, where the snap of catches is changing the manner in which individuals think, design and execute their works and experience their lives, virtual reality, surrealism, hyper reality are the terms in vogue. They are so commonly utilized wherever that they may not appear to be whimsical any more. In any case, the fervor in superstitions, magic in such a context the novel by Chitra Banerjee Divakaruni, The Mistress of Spices, is a superb perused which besieges the faculties and shivers the craving with its fascinating utilization of spices.